The Impact of Dividend Policy on Firm Performance in Public Listed Company in Malaysia - Kim Foong, Jee; Nurul Izza, Abd Malek (HUMAN RESOURCE MANAGEMENT ACADEMIC RESEARCH SOCIETY, 2022)
The aim of this study is to investigate the relationship between dividend policy and firm performance in Public listed company in Malaysia. The sample collected for this study covered 8 years from 2011 to 2018. This study will focus one of the subsectors from consumer product and service sector which listed in Bursa Malaysia. The total observation was 200. This study used two measurements for firm performance which are return on equity (ROE) and return on asset (ROA). The measurement of dividend policy is earning per share (EPS), dividend pay-out ratio (DPR) and price earnings ratio (PER). Based on the findings, there is significant relationship between EPS with ROE and ROA. For PER, there is an insignificant relationship with ROE but it has significant relationship with ROA. However, DPR has insignificant relationship with ROE and ROA. The result from this study will brings advantage and usefulness for investor as well as policy marker for in Malaysia because it provides better understandings and knowledge on dividend policy on firm performance for consumer product and service sector in Malaysia.